Reliability of the 3-component model of aerobic, anaerobic lactic, and anaerobic alactic energy distribution (PCr-LA-O2) for energetic profiling of continuous and intermittent exercise - Kaufmann, S.; Latzel, R.; Beneke, R.; Hoos, O. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To assess the test-retest reliability of the continuous (PCr-LA-O2) and intermittent (PCr-LA-O2int) version of the 3-component model of energy distribution in an applied setting.